COGNITIVE REHABILITATION FOR REDUCED COGNITIVE IMPAIRMENT: EFFICACY ASSESSMENT IN PATIENTS WITH TRAUMATIC BRAIN INJURY (Contemporary Journal of Social Science Review, 2025)
The present study assessed the effectiveness of a 12-week cognitive rehabilitation program in improving cognitive functions for people who have suffered traumatic brain injury (TBI). To conduct this study, 40 patients with TBI were selected using purposive sampling from hospitals in Lahore, Pakistan, and divided into 2 groups based on random assignment. One group was named as the experimental group (n=20) and received cognitive rehabilitation in addition to their standard medical care. The other group served as the control group (n=20) and received only standard medical care. Participants in both groups were assessed on Mini-Mental State Examination (MMSE) to assess their level of cognitive impairment at baseline and at post intervention levels. The main findings from this research showed there were statistically significant improvements in the intervention group's performance when assessed on the MMSE at post intervention level, specifically in the domains of Registration, Attention, Memory, and Language, but not in Orientation domain. There were no statistically significant pre-post differences for the control group's scores on the assessed cognitive domains. This research provides evidence that structured cognitive rehabilitation is beneficial for improving cognitive functions in patients with TBI and therefore emphasizes the importance of cognitive rehabilitation in Pakistan’s neurorehabilitation practice